The Role of Geopolitical Components in Afghanistan's National Power - IHSAN, Ihsan Ullah; YAR, Fayaz Gul Mazloum (Indonesia Strategic Sustainability, 2024)
Purpose:This research investigates the intricate relationship between geopolitical factors and Afghanistan's national power, offering valuable insights into the nation's standing on the global stage. Our findings underscore the pivotal role of national unity, with 96% of respondents recognizing its significance. It reaffirms the historical resilience of the Afghan people in the face of external pressures and internal divisions.Methodology:Besides national unity, the study identifies several other influential geopolitical components, including leadership, Aryan culture, human resources, and geographical location. These components interweave with Afghanistan's historical, cultural, and geographic context, collectively shaping its national power. Notably, while historically significant, religion and natural resources were perceived as less influential, challenging conventional notions about their impact.Findings:The research also highlights the dynamic nature of Afghanistan's national power, with new geopolitical factors, such as